Neoadjuvant chemotherapy in invasive lobular carcinoma of the breast: perspectives based on the survival outcomes - Gauthier, Virginie; Simard, Anne-Julie; Desbiens, Christine; Poirier, Brigitte; Boudreau, Dominique; Leblanc, Dominique; Morin, Claudya; Hogue, Jean-Charles; Poirier, Éric (Frontiers in Oncology, 2025)
Whether patients with invasive lobular carcinoma (ILC) can benefit from neoadjuvant chemotherapy (NAC) remains uncertain. In order to attempt to bring some light on the matter, the patients treated for ILC between 1998 and 2016 at a tertiary center specialized in breast diseases were examined according to NAC vs. adjuvant therapy. Among 265 eligible women treated for ILC, 72 received NAC and 193 received adjuvant chemotherapy. In the NAC group, only 4.2% of the patients with ILC achieved a pathological complete response after NAC. Over a mean follow-up of 8 years, after adjusting for confounders (age >55, T-stage, N-stage, surgery type, radiotherapy, and hormonal therapy), the two groups had similar 10-year locoregional recurrence rates (NAC: 90.6%; adjuvant: 93.5%, P=0.110), but the NAC group showed lower 10-year recurrence-free survival (51.8% vs. 72.7%, P=0.0004), 10-year progression-free survival (59.3% vs. 82.0%, P<0.0001), and 10-year overall survival (56.2% vs. 80.7%, P<0.0001). The results suggest that the response of ILC to NAC is poorer than to adjuvant chemotherapy. It is the authors’ opinion that ILC should be considered separately from IDC in clinical trials and guidelines, and that patients with ILC might benefit from a more aggressive surgical approach followed by adjuvant chemotherapy no matter the severity of the disease.